Personal Predictors of Future Teachers’ Tolerance of Uncertainty - Halian , Ihor (Insight: the psychological dimensions of society, 2023)
The purpose of the research is to analyze the predictorsthat forecast the emergence of tolerance of uncertaintyas future teachers’ integral personal trait. Methods: MultipleStimulus Types Ambiguity Tolerance-1 (MSTAT-1)McLain (adapted by E. Osin), which diagnoses toleranceof uncertainty; linear multiple regression to determinethe effect of various predictors on the dependent variable.The total research sample consisted of 72 futureteachers of the “Primary Education” specialty. The sampleis homogeneous, formed randomly. Results. Therole of various predictors in the formation of futureteachers’ tolerance of uncertainty is shown. Semi-partialcorrelation (correlation of components) as an elementof multiple regression analysis proved that “attitude touncertain situations” (r = .532, p≤.01; R2 = .283 (28.0%of the explained variance)) and “preference for uncertainty”r = -.447; p≤.01; R2 = .199 (20.0%)) are dominant in explaining the variability of the dependent variable“tolerance of uncertainty”. Predictors of “attitude to novelty”(r = .376; p≤.01; R2 = .141 (14.0%)) and “attitudeto complex tasks” (r = .340; p≤.01; R2 = .115 (12.0%))although they have a statistically significant correlation,the strength of its connection and the percentageof explained dispersion are smaller than in thosedescribed above. Discussion and conclusions. Toleranceis an integral characteristic of a person, whichinvolves acceptance of the individuality of another personand one’s own personality. An average with a tendencyto low level of manifestation of tolerance of uncertaintywas diagnosed in higher education graduates inthe pedagogical field. This is the result of lack of futureteachers’ experience of interaction with uncertaintyand overcoming difficulties caused by it. The resultsof the multiple regression analysis proved that such predictorsas “attitude to uncertain situations” and “preferencefor uncertainty” had the greatest influence onthe expression of tolerance of uncertainty.
Keywords: multiple equations, tolerance of uncertainty, decision-making, creative motivation, professional orientation, future teachers